SOME ASPECTS OF PSYCHOLOGICAL CARE FOR PERSONS DEPENDING ON PSYCHOACTIVE SUBSTANCES (SAS) - Avanesyan, G. G. (Modern Psychology, 2019)
This article discusses the problem of dependence on psychoactive substances, the growth of drug addiction in the world, methods of providing medical and psychological assistance. It describes the forms of physical and psychological dependence on psychoactive substances, the international program for the rehabilitation of drug addicts according to the program of 12 steps, which has been successfully implemented in recent years in Russia too, which allows drug addicts to be in prolonged remission.